2015
DOI: 10.1002/smll.201501473
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of 2D Heterojunction in Graphene via Low Energy N2+ Irradiation

Abstract: Substitutional doping in graphene is locally induced with very low energy nitrogen ions. Irradiated and nonirradiated areas exhibit different charge carrier densities and are separated by a sharp boundary, stable up to 750 °C. The way towards lithographic control of the electronic properties of graphene by ion irradiation is paved, providing a proof of principle for the fabrication of 2D graphene-based heterojunctions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…The layer was eventually annealed to 550 K to reduce the amount of implanted nitrogen. Higher temperature annealing was not performed to avoid the possible depletion of pyridinic N, as reported for G/Ir(111) [30]. CO was dosed by backfilling the chamber with a doser close to the sample [15,16,28].…”
Section: Methodsmentioning
confidence: 99%
“…The layer was eventually annealed to 550 K to reduce the amount of implanted nitrogen. Higher temperature annealing was not performed to avoid the possible depletion of pyridinic N, as reported for G/Ir(111) [30]. CO was dosed by backfilling the chamber with a doser close to the sample [15,16,28].…”
Section: Methodsmentioning
confidence: 99%
“…Following this strategy, recent studies revealed the actual possibility of introducing doping defects in graphene to tune its properties. [1][2][3] For example, by adding proper gaseous precursor during the Chemical Vapor Deposition (CVD) process 4 or by means of low-energy ion implantation, 5,6 substitutional nitrogen atoms can be trapped inside carbon vacancies, strongly modifying the graphene electronic structure. 7 New functionalities are predicted to arise when transition metal dopants are introduced.…”
Section: Introductionmentioning
confidence: 99%
“…Such balance is likely related to the doping technique: adding N atoms during growth conditions favours the dynamic selection of defects with lower energy, with no constraint posed by the local abundance of N atoms required. Conversely, other doping techniques such as post-growth ion implantation favour defects with a different graphitic/pyridinic ratio, as a consequence of the ballistic formation process [21,47,48].…”
Section: Resultsmentioning
confidence: 99%